A new species of Maculambrysus Reynoso & Sites, 2021 (Hemiptera: Heteroptera: Naucoridae) from an aguaje palm swamp in southeastern Peru - Sites, Robert W. (Zootaxa, 2023)
The neotropical saucer bug genus Maculambrysus Reynoso & Sites is currently represented by five species from Tabasco, México to Pará, Brazil. Presented here is the description of a sixth species, Maculambrysus gallicei n.sp., which was collected from rootmats and leafpacks in an aguaje palm swamp in southeastern Peru. It can be distinguished from most congeners by the concolorous dark-brown hemelytra and the mottled orange-brown pronotum, as well as characteristics of the male accessory genitalic process of tergum VI, and female subgenital plate and laterosternites VI. Other aquatic Heteroptera co-occurring with this new species are given.